Correlation between Grade in Transitional Cell Carcinoma (TCC) and Expression of Epidermal Growth Factor Receptor (EGFR) - MR Jallali Nadoushan; F Heidary; F Zaeri; H Ahmadi (Tehran University of Medical Sciences, 2007)
Background: The present study was undertaken to investigate the correlation of Epidermal Growth Factor Receptor (EGFR) expression with grade of Transitional Cell Carcinoma (TCC). Methods: Tumor samples of 75 patients from Mostafa Khomaini Hospital with Transitional Cell Carcinoma of the bladder were analyzed by immunohistochemistry for expression of EGFR. In this context, we assigned the bladder tumors a grade accord¬ing WHO classification. Results analyzed for possible correlation with the expression status of the Epidermal Growth Factor Receptor (EGFR). Results: This cross-sectional study showed that all grades of Transitional Cell Carcinoma expressed EGFR, and 14 cases were LMP (18.9%) which 10 cases among them had negative cells according EGFR point of view(71.4%) and 4 cases had re¬ported positive (28.6%). Thirty five cases were low grade (46.7%) which 18 cases among them had reported negative cells (51.4%) and 17 cases had positive cells (48.6%). Twenty six cases were high grade (34.7%) that 9 cases among them had reported negative cells (34.6%). Seventeen cases had positive cells (65.4%). Mann-Witney test showed relation between grade and expression of EGFR (P